A COMPREHENSIVE ASSESSMENT OF REHABILITATION SERVICES AND RECIDIVISM REDUCTION EFFORTS IN OGUN STATE PRISONS: INSIGHTS FROM THE NIGERIAN CONTEXT - Wasiu , Olufemi Johnson (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study presents a comprehensive assessment of the availability and adequacy of rehabilitation programs in correctional facilities in Ogun State, Nigeria, with a focus on their impact on recidivism reduction. The research employed a descriptive survey research design, involving on-site observations, questionnaire administration, and interviews conducted in selected correctional facilities across Southwestern Nigeria. The objective was to determine the extent to which rehabilitation programs are accessible to inmates and whether they effectively contribute to their reintegration into society. Findings indicate that while certain rehabilitation programs, including religious activities, counseling, recreation, and case work, are consistently available across sampled correctional facilities, there are notable disparities. Academic programs, such as adult literacy and SSCE remedial courses, were observed in some facilities, while vocational training, such as carpentry and tailoring, were widely available. However, the provision of after-care programs was limited, with only tools, financial, and technical support being offered in select facilities. Notably, inmate commissary and case work were lacking, as some inmates reported no knowledge of legal aid. Insights from recidivist inmates suggest the need for enhanced support systems post-release. The study concludes that, while rehabilitation programs are present in Ogun State correctional facilities, a significant focus on after-care services is necessary to provide adequate support for inmates as they transition back into society. This research contributes valuable insights into the state of rehabilitation services in Nigerian correctional facilities and their potential role in reducing recidivism.